49.1k views
0 votes
Can you please help me
simplify
3.2y+4.3y−6.1(y−1)
thanks

User Sleeyuen
by
5.3k points

2 Answers

2 votes

Let's simplify step-by-step. Hope I help :)

3.2y+4.3y−6.1(y−1)

Distribute:

=3.2y+4.3y+(−6.1)(y)+(−6.1)(−1)

=3.2y+4.3y+−6.1y+6.1

Combine Like Terms:

=3.2y+4.3y+−6.1y+6.1

=(3.2y+4.3y+−6.1y)+(6.1)

=1.4y+6.1

Answer:

=1.4y+6.1

User Goric
by
5.4k points
1 vote

Factor out the -6.1(y-1)

So 6.1y-7.1

-6.1y+3.2y+4.3y=1.4y

1.4y + 6.1. is the answer.

User Zenzelezz
by
5.6k points